2020
DOI: 10.1038/s41467-020-16337-y
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-derived extracellular vesicles from Plasmodium vivax patients signal spleen fibroblasts via NF-kB facilitating parasite cytoadherence

Abstract: Plasmodium vivax is the most widely distributed human malaria parasite. Previous studies have shown that circulating microparticles during P. vivax acute attacks are indirectly associated with severity. Extracellular vesicles (EVs) are therefore major components of circulating plasma holding insights into pathological processes. Here, we demonstrate that plasma-derived EVs from Plasmodium vivax patients (PvEVs) are preferentially uptaken by human spleen fibroblasts (hSFs) as compared to the uptake of EVs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 48 publications
3
70
1
1
Order By: Relevance
“…CD71 is the major component of reticulocyte-derived exosomes ( Harding Stahl, 1983 ; Pan et al, 1985 ; Díaz-Varela et al, 2018 ) and it is a reticulocyte-specific receptor for P. vivax ( Gruszczyk et al, 2018 ). Importantly we have recently shown by mass spectrometry-based proteomics and molecular profiling that CD71 is a component of circulating EVs from P. vivax patients ( Toda et al, 2020 ). Therefore, we used it as a surrogate molecular marker of EVs derived from P. vivax -infected reticulocytes for selection of SEC fractions from individual patients ( Supplementary Data Sheet 4A ) and healthy donors ( Supplementary Data Sheet 4B ) to compose a pool of vesicles for spleen cells interaction experiments.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…CD71 is the major component of reticulocyte-derived exosomes ( Harding Stahl, 1983 ; Pan et al, 1985 ; Díaz-Varela et al, 2018 ) and it is a reticulocyte-specific receptor for P. vivax ( Gruszczyk et al, 2018 ). Importantly we have recently shown by mass spectrometry-based proteomics and molecular profiling that CD71 is a component of circulating EVs from P. vivax patients ( Toda et al, 2020 ). Therefore, we used it as a surrogate molecular marker of EVs derived from P. vivax -infected reticulocytes for selection of SEC fractions from individual patients ( Supplementary Data Sheet 4A ) and healthy donors ( Supplementary Data Sheet 4B ) to compose a pool of vesicles for spleen cells interaction experiments.…”
Section: Resultsmentioning
confidence: 99%
“…However, the increased interaction observed in DCs when whole splenocytes were in contact with PKH-labeled Pv EVs can reflect its specific phagocytosis. Indeed, we have previously demonstrated that human reticulocyte-derived exosomes are specifically taken up by DCs in a Siglec-1-dependent manner ( Díaz-Varela et al, 2018 ) and circulating EVs in patients with acute P. vivax infection contain parasite proteins ( Toda et al, 2020 ). In the absence of supportive evidence, this remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations